THE EFFECTIVENESS OF THE SYSTEMS AND PROCEDURES OF THE PARKING TAX REVENUE AT REGIONAL REVENUE OFFICE OF MANADO - Prabowo, Ahmad Arif; Pusung, Rudy J. (Universitas Sam Ratulangi, 2015)
Parking tax is tax on the operation of parking outside of the road, provided both related to the subject of business or provided as a business, including the provision of day care vehicles. The effectiveness indicates the level of achievement of a goal, an attempt is said to be effective if there are efforts to achieve its objectives. Act No.59 Year 2007 on Regional Financial Management Guidelines regulate the procedures for the implementation of the reception area which is managed by the treasurer reception. The purpose of this study to determine how the effectiveness of tax revenue as well as how System Parking Parking Tax Revenue Procedure In Manado City Regional Revenue Office (DISPENDA). The method used is the descriptive analysis. Data are obtained through field studies. The results of this research is the effectiveness of the city parking tax receipts Manado has been very good with an average achievement of 110.80% for the last 5 years. Parking Tax Revenue Procedure System in Manado City DISPENDA is in accordance with Regulation No.59 of 2007. It is expected that in the next year, the management of DISPENDA can maximize the realization of parking tax through data collection and dissemination on the taxpayer as well as continue to follow the Rules and Procedures governing the System Acceptance PAD especially on parking tax. Â Keywords: effectiveness, revenue procedure system, parking tax